Recurrence, Reactivation, or Inflammatory Rebound of SARS-CoV-2 Infection With Acute Vestibular Symptoms: A Case Report and Revision of Literature - Zaffina, Salvatore; Lanteri, Paola; Gilardi, Francesco; Garbarino, Sergio; Santoro, Annapaola; Vinci, Maria Rosaria; Carsetti, Rita; Scorpecci, Alessandro; Raponi, Massimiliano; Magnavita, Nicola; Camisa, Vincenzo (Frontiers in Human Neuroscience, 2021)
A case of recurrent coronavirus disease 2019 (COVID-19) with neurovestibular symptoms was reported. In March 2020, a physician working in an Italian pediatric hospital had flu-like symptoms with anosmia and dysgeusia, and following a reverse transcription PCR (RT/PCR) test with a nasopharyngeal swab tested positive for SARS-CoV-2. After home quarantine, 21 days from the beginning of the symptoms, the patient tested negative in two subsequent swabs and was declared healed and readmitted to work. Serological testing showed a low level of immunoglobulin G (IgG) antibody title and absence of immunoglobulin M (IgM). However, 2 weeks later, before resuming work, the patient complained of acute vestibular syndrome, and the RT/PCR test with mucosal swab turned positive. On the basis of the literature examined and reviewed for recurrence cases and vestibular symptoms during COVID-19, to our knowledge this case is the first case of recurrence with vestibular impairment as a neurological symptom, and we defined it as probably a viral reactivation. The PCR retest positivity cannot differentiate re-infectivity, relapse, and dead-viral RNA detection. Serological antibody testing and viral genome sequencing could be always performed in recurrence cases.